CARBARYL INDUCED TESTICULAR TOXICITY IN MALE RATS AND THE PROTECTIVE EFFECT OF MUCUNA PRURIENS (L) - SUNDARARAJAN MADHUMATHI; GANAPATHY MURUGAN ALAGU LAKSHMANAN; RAJARAM PANNERSELVAM (International Journal of Pharma and Bio Sciences, 2013)
Cow-hedge (Mucuna pruriens L.) is one of the potential tropical legumes having good medicinal properties. The aim of our present study was to investigate the testicular protective activity of methanolic extract of Mucuna pruriens (MEMP) seeds against carbaryl induced testicular toxicity in rats. The MEMP at the dose of 300 mg/kg of body weight were administered orally once daily for 28 days to the infertility induced male rats. Sperm count, sperm motility and abnormality were analyzed. Further histopathological examination of the testes section was carried out to support the induction of testicular carbaryl toxicity , and testicular protective efficacy of methanolic extract of seeds of Mucuna pruriens plants treated with propiconazole and ABA.. The extract showed potent activities on sperm count, motility and abnormality. The histopathological observation supports the biochemical evidence of testicular protection of MEMP further strengthen the testicular protective observation of MEMP. The results of the present study strongly revealed that MEMP has potent testicular protective activity against carbaryl induced testicular damage in experimental rats.